TIPOLOGI SETTING DAN AKTIVITAS REKREASI DI SEPANJANG TUKAD BADUNG, KOTA DENPASAR - Persada, Nyoman Gema Endra (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 2 No 1 (2015): April 2015, 2014)
Abstract The Revitalization of Badung River has provided a significant waterfront for Denpasar . Having been used for irresponsibly disposed waste, this river has now emerged as a significant public space. It has promoted diverse recreational activities engaged by urban dwellers of both Denpasar and its surrounding areas. This paper analyses the relationship between numerous spatial settings along the river and their contained recreational activities. The potential attraction of each spatial setting is evaluated by the presence of one or more of the following elements, visible sceneries; aesthetic plants; shade trees; fish; planned space; abandoned or/and vacant  land. Meanwhile, type of activities pertained to recreational function of this waterfront include relaxing; sitting around; fishing; chatting; snacking; resting after work; ceremonial activities; and food vendoring (permanent and non-permanent). The research then makes a connection between each spatial element and activities to draw certain relationships between space and its use. Keywords: Badung River, public space, spatial setting, recreational activities Abstrak Kegiatan revitalisasi Sungai Badung telah menghasilkan daerah aliran sungai yang penting bagi Kota Denpasar. Setelah sekian lama dimanfaatkan sebagai tempat pembuangan limbah kota, area ini muncul sebagai ruang publik yang signifikan. Area ini mengundang terjadinya beragam aktivitas rekreasi yang dilaksanakan baik oleh penduduk kota yang berasal dari Denpasar dan area-area di sekitarnya. Paper ini menganalisa hubungan antara beragam setting keruangan yang terjadi di sepanjang aliran sungai ini dengan aktivitas rekreasi yang terjadi di dalamnya. Ketertarikan dari setiap spasial setting dievaluasi berdasarkan keberadaan dari satu atau lebih elemen-elemen berikut ini: pemandangan ( view ); tanaman hias; pohon peneduh; ikan hias berenang dalam aliran air sungai; ruang-ruang yang direncanakan; dan ruang-ruang tidak/belum terencanakan. Sementara itu, kegiatan rekreasi yang telah terjadi adalah: bersantai; duduk-duduk; bersenda gurau; memancing; menikmati makanan kecil; istirahat dari kerja; upacara keagamaan; dan berjualan makanan kecil. Penelitian ini kemudian mengkorelasikan antara ruang serta kegiatan yang terjadi dalam rangka mengkaji hubungan antara tempat dan pemakainya. Kata kunci: Tukad Badung, ruang publik, setting keruangan, aktivitas rekreasi
Keywords: Tukad Badung, ruang publik; setting keruangan; aktivitas rekreasi